Association of Parenting Practices and Animal - Soure Protein Intake with Stunting Among Children Aged 24–59 Months - Kurata A’yuni; Dea Zara Avila; Juraidin Juraidin; Nur Husnul Khatimah (MESINA (Medical Scientific Journal), 2026)
Stunting remains a major public health and nutritional problem affecting children worldwide, including Indonesia. Stunting is a condition of impaired growth resulting from chronic malnutrition and recurrent infections, characterized by a height-for-age index below the standard established by the World Health Organization (WHO). Parenting practices and adequate animal protein intake are important factors influencing child growth and development. Inadequate caregiving and insufficient consumption of animal-source foods may increase the risk of stunting among children under five years of age. This study aims to analyze the relationship between parenting practices and animal protein intake with the incidence of stunting among children aged 24–59 months in the working area of Woha Public Health Center, Bima Regency. The study will employ an analytical observational design with a cross-sectional approach. The population consists of 399 children aged 24–59 months, and a sample of 80 respondents will be selected using simple random sampling based on the Slovin formula with a 10% margin of error. Data on parenting practices and animal protein intake will be collected through structured questionnaires, while stunting status will be determined using anthropometric measurements based on the Height-for-Age Z-score (HAZ) indicator. Data will be analyzed using descriptive statistics and the Chi-Square test to determine the relationship between variables. The findings of this study are expected to provide scientific evidence regarding the influence of parenting practices and animal protein intake on stunting incidence and serve as a reference for developing nutrition and child health intervention programs aimed at reducing stunting prevalence in the Woha Public Health Center area.